NAVIGATING SHARIA COMPLIANCE IN FINTECH STARTUPS: LEGAL CHALLENGES AND OPPORTUNITIES IN THE UNITED KINGDOM - Daniel Wilson; Lucy Taylor; Thomas Harris (Sharia Oikonomia Law Journal, 2025)
The rapid growth of fintech innovation in the United Kingdom has created new pathways for financial inclusion, particularly among Muslim consumers seeking Sharia-compliant alternatives. However, the integration of Islamic financial principles within a secular regulatory framework presents legal ambiguities and operational challenges for fintech startups. The existing legal environment in the UK does not explicitly accommodate Sharia compliance, creating uncertainties for emerging Islamic fintech ventures. This study aims to examine the legal barriers and institutional opportunities for achieving Sharia compliance in UK-based fintech startups. A qualitative legal research methodology was employed, involving doctrinal analysis of UK financial regulations, Islamic jurisprudential sources, and policy reports, complemented by expert interviews with fintech entrepreneurs, Sharia scholars, and legal professionals. The findings reveal a significant regulatory gap concerning the certification, standardization, and recognition of Sharia-compliant fintech models. However, opportunities exist through regulatory sandboxes, ethical finance frameworks, and collaboration with private Sharia advisory boards. The study concludes that legal innovation, inter-institutional dialogue, and policy refinement are critical to fostering a viable ecosystem for Islamic fintech in the UK. Recommendations include developing a hybrid compliance model and enhancing regulatory clarity to support both innovation and religious integrity.